Beyond Cost Benefit Analysis: A SAM-CGE Model for Project-Program Evaluation - Scandizzo, Pasquale Lucio; Cufari, Daniele (American Journal of Management, 2024)
This paper presents a new methodology of project evaluation based on the use of a social accounting matrix (SAM). The proposed method considers both the project as an autonomous shock and an endogenous activity, thus capturing both the demand and the supply side effects that can be associated with investment. In assessing project impact, these two effects have to be considered complementary, even though they may be combined in different proportions and with different strength in different practical cases. The autonomous dimension is however a distinctive feature of a project as an economic concept. Its consideration has important implications for assessing a project’s structural impact as an activity ranging from complete isolation to total embeddedness in the economic system. The paper also shows that both in its construction and operational phases the project displays structural effects on the economic system and that these effects may be sizable and partly offsetting the project’s direct impact on demand and supply variables.